Mejora al proceso de gestión y control de inventarios de lubricantes en la Refinería de Cartagena (2023)
This research aims to deliver a proposal to improve the management and inventory control of lubricants in the Cartagena Refinery. This initiative stems from the opportunities for improvement detected by the author of this research throughout his working life at the Refinery facilities and that, for purposes of standardizing processes, the results of this research could be replicated at the Refinery. Barrancabermeja. For this, it is important to mention that the development of said proposal entails in a first scenario, the realization of a diagnosis of the current state of the management of the inventories of the lubricants that are used in the Refinery for the lubrication of the machinery, as well as, the application of the ABC classification method for inventories which allows prioritizing inventory management. Finally, strategies will be proposed to improve the management and control of lubricant inventories at the Refinery